2015
DOI: 10.1016/j.wem.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Russula subnigricans Poisoning: From Gastrointestinal Symptoms to Rhabdomyolysis

Abstract: Wild mushroom poisoning is often reported to cause acute liver or renal failure. However, acute rhabdomyolysis caused by wild mushroom poisoning has rarely been reported. We describe 7 patients of 1 family with Russula subnigricans Hongo poisoning. Their clinical manifestations varied from gastrointestinal symptoms to rhabdomyolysis, with 1 fatality. Our report provides supporting evidence that rhabdomyolysis may result from ingestion of R subnigricans mushrooms. A key to survival for patients with rhabdomyoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 13 publications
1
36
1
Order By: Relevance
“…Russula subnigricans is one of the most toxic wild mushrooms in the world, which can cause rhabdomyolysis (Lin et al 2015). Some cytotoxic substances such as Russuphelin A, B, C, D, E, F were isolated from R. subnigricans, which Russuphelin were cytotoxic to various solid tumor cells (Takahashi et al 1992(Takahashi et al , 1993.…”
mentioning
confidence: 99%
“…Russula subnigricans is one of the most toxic wild mushrooms in the world, which can cause rhabdomyolysis (Lin et al 2015). Some cytotoxic substances such as Russuphelin A, B, C, D, E, F were isolated from R. subnigricans, which Russuphelin were cytotoxic to various solid tumor cells (Takahashi et al 1992(Takahashi et al , 1993.…”
mentioning
confidence: 99%
“…[ 14 ] Many patients with non-amatoxin containing mushroom poisoning also present with gastroenteritis. [ 15 17 ] In a previous report, 82.7% of cases involving mushroom intoxication were attributed to an unknown species of mushroom. [ 7 ] It has been suggested that delayed gastroenteritis symptoms after the ingestion of mushrooms is indicative of amatoxin poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 One study in humans did not find evidence of T. equestre toxicity and support that T. equestre is edible if ingested in reasonable amounts by healthy people. 15 Mushroom poisoning with rapid onset myotoxicity is associated with ingestion of selected Russula species, including R. subnigricans 2,[16][17][18] or Russula subnigricans Hongo. The causative toxin has been reported as a highly strained carboxylic acid, cycloprop-2-ene carboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…20 Clinically, myotoxic mushroom-poisoned patients typically present with fatigue, myalgia, muscle weakness and dark urine representing rhabdomyolysis, with or without obvious gastrointestinal (GI) symptoms. [8][9][10][11][16][17][18] Some patients with severe illness develop acute renal failure, electrolyte disturbances (hyperkalaemia, hypocalcaemia), respiratory failure, acute myocarditis, cardiac arrhythmias, pulmonary oedema, cardiac failure or cardiovascular collapse. 8,11,[16][17][18] Fatalities have been reported from myotoxic mushroom poisoning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation